Sams teach yourself Microsoft SQL Server 2005 Express in 24 hours - Balter, Alison (Sams teach yourself., 2006)
Written with clarity and a down-to-earth approach, Sams Teach Yourself SQL Server 2005 Express in 24 Hours covers the basics of Microsoft's latest version of SQL Server. Expert author Alison Balter takes you from basic concepts to an intermediate level. You will learn all of the basic tasks necessary for the administration of SQL Server 2005. You will also learn how to write and fully utilize SQL Server stored procedures, functions, and triggers using T-SQL, VB.NET, and C♯. Finally, you will learn how to output SQL Server data to reports, and the Internet.